2019
DOI: 10.1007/s13205-019-1725-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant defensins: types, mechanism of action and prospects of genetic engineering for enhanced disease resistance in plants

Abstract: Natural antimicrobial peptides have been shown as one of the important tools to combat certain pathogens and play important role as a part of innate immune system in plants and, also adaptive immunity in animals. Defensin is one of the antimicrobial peptides with a diverse nature of mechanism against different pathogens like viruses, bacteria and fungi. They have a broad function in humans, vertebrates, invertebrates, insects, and plants. Plant defensins primarily interact with membrane lipids for their biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 113 publications
0
43
0
1
Order By: Relevance
“…C. glabrata, which does not contain this fungus-specific ceramide, is not inhibited. This peptide and its analogs (e.g., NaD1, Rs-ARF1, SPE10) have little cytotoxicity against mammalian cells at dosages that are inhibitory to fungal pathogens (Matejuk et al, 2010;Sher Khan et al, 2019).…”
Section: Selective Activity On Membranesmentioning
confidence: 99%
“…C. glabrata, which does not contain this fungus-specific ceramide, is not inhibited. This peptide and its analogs (e.g., NaD1, Rs-ARF1, SPE10) have little cytotoxicity against mammalian cells at dosages that are inhibitory to fungal pathogens (Matejuk et al, 2010;Sher Khan et al, 2019).…”
Section: Selective Activity On Membranesmentioning
confidence: 99%
“…It is an effective way to introduce genes with good performance to solve this problem. Broad-spectrum and stable resistance make AMPs candidates for transgenic breeding [21,36]. Our earlier works demonstrated that transgenic wheat plants expressing exogenous AMP genes exhibited increased resistance to fungal pathogens, such as Gaeumannomyces graminisvar.…”
Section: Discussionmentioning
confidence: 99%
“…Some AMPs can directly affect cell membranes of fungi and change their structure, thereby inhibiting growth of the fungi [16][17][18]. For instance, Rs-AFP1, Rs-AFP2 and Rs-AFP3/4, isolated from seeds of Raphanus sativus, are the most in-depth-studied antimicrobial peptides in plant disease resistance [19][20][21]. Some studies have shown that Rs-AFP2 can resist to a variety of fungal diseases, such as rice sheath blight, rice blast, wheat sharp eyespot and fusarium head blight [13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Another form of cyclization that is found abundantly in natural HDPs, mainly in defensins, is the disulfide intramolecular cross-link between cysteine residues, which has been shown to enhance proteolytic stability (157)(158)(159)(160). Inspired by the nature, Scudiero et al (160) engineered a 17-residue cyclic synthetic hybrid HDP, based on the internal hydrophobic domain of human-beta defensin (HBD)-1 and positively charged C-terminal of HBD-3 (RRKK residues), and demonstrated good antimicrobial efficacy against Gram-positive and Gramnegative bacteria and herpes simplex virus, with low toxicity and good proteolytic stability.…”
Section: Cyclizationmentioning
confidence: 99%